Peran Kepemimpinan Dalam Mobilisasi Gerakan Human initiative Di Kota Bengkulu - Setiawan, Deni; Yogopriyatno, Jatmiko; Hardayani, Yorry (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2024)
In facing the challenges of poverty and low education levels in Bengkulu Province, the HOME Learning Center program is an important intervention to increase the capacity of orphans and poor children. In the context of social movements, leadership has a crucial role in inspiring, building commitment, and mobilizing resources. Therefore, this study aims to describe the role of leadership in advancing the Human initiative movement in Bengkulu City, especially in quality education programs for orphans. Through qualitative research methods using observation, interviews, and documentation, this study highlights the contribution of the Head of Human initiative Volunteer (HIVE) Bengkulu in inspiring members, mobilizing resources, and building a wide network to support the program. The results show that the leadership applied by the chairman of HIVE is democratic and participatory, which respects the opinions and abilities of each member, and empowers them according to their respective interests and expertise. The recommendations put forward to maintain the contribution of leadership in advancing the Human initiative movement in Bengkulu City are to develop sustainable leadership training programs and fostering generations of young leaders.